2020
DOI: 10.1017/jfm.2020.679
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale structure transitions in turbulent Taylor–Couette flow

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…These are the first investigations of this geometry on counter-rotating cylinders, so the existence of TVF and WVF for these parameters is proven by our study, while also detached flows had been observed for narrow gaps, also this is proven for this strongly differing system. The ACV as a stable oscillating pattern is a newly made observation in TC flow, although similar singular structures had been made in other studies [20].…”
Section: Flow Patternssupporting
confidence: 71%
“…These are the first investigations of this geometry on counter-rotating cylinders, so the existence of TVF and WVF for these parameters is proven by our study, while also detached flows had been observed for narrow gaps, also this is proven for this strongly differing system. The ACV as a stable oscillating pattern is a newly made observation in TC flow, although similar singular structures had been made in other studies [20].…”
Section: Flow Patternssupporting
confidence: 71%
“…These studies also investigated the mechanisms that exist for large enough Reynolds number, for momentum transport in the anticyclonic range with changing rotation number, with these findings largely supported by the later experimental observations of Kawata & Alfredsson (2019). Similar results for the angular momentum transfer in TCF were found both in the numerical simulations of Brauckmann et al (2016) and in the experimental observations of Tokgoz et al (2020).…”
Section: Introductionsupporting
confidence: 64%
“…[49,83]) as well as fully turbulent flows (e.g. [84]), and particle suspensions [85,86], most of the time in false(rzfalse) vertical planes (see figure 2). The challenge in applying PIV to elasto-inertially turbulent flows resides, as for conventional turbulence, in the high-flow velocities and short-lived flow structures that need to be captured requiring high-speed systems to achieve good temporal resolution [84].…”
Section: Flow Configuration Key Parameters and Experimental Methodsmentioning
confidence: 99%
“…[84]), and particle suspensions [85,86], most of the time in false(rzfalse) vertical planes (see figure 2). The challenge in applying PIV to elasto-inertially turbulent flows resides, as for conventional turbulence, in the high-flow velocities and short-lived flow structures that need to be captured requiring high-speed systems to achieve good temporal resolution [84]. For that purpose, laser Doppler velocimetry (LDV) was used by [53] to access local velocity information within the gap at high temporal resolution.…”
Section: Flow Configuration Key Parameters and Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation